Strategy to Increase Awareness of MSMEs Halal Certificates in Islamic Sharia-Compliant Provinces: Case Study in Aceh Province - Muhammad Syahrizal, Teuku; Umuri, Khairil; Halim, Hendra (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This research delves into developing strategies to augment awareness of Micro, Small, and Medium Enterprises (MSMEs) halal certificates in Islamic sharia-compliant provinces, focusing on the case of Aceh Province. Given the increasing global demand for halal products, bolstering awareness of the certification process is paramount. The study employs a robust SWOT Analysis, encompassing Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) assessments, to comprehensively evaluate the existing landscape. Internal strengths, weaknesses, and external opportunities and threats pertinent to MSMEs halal certificates are systematically examined. By harnessing internal strengths and mitigating weaknesses, this research seeks to address external challenges and harness opportunities for strategic planning proactively. The outcomes aim to provide actionable insights for various stakeholders, including MSMEs, government entities, halal certifiers, and industry regulators, fostering a collaborative environment for improving the perception and understanding of MSMEs halal certificates. Furthermore, this study emphasizes the vital role of Aceh Province as a case study, shedding light on practical strategies that similar regions can adopt to bolster the halal industry's growth while aligning with Islamic economic principles and values. The findings underscore the need for a proactive approach to ensuring the sustainability and expansion of MSMEs halal certifications in Sharia-compliant provinces.